Laity : frontier ministers of the church - Lang-akan, Benny P. ([Quezon City, Phils.] : St. Andrew's Theological Seminary, 1993)
" The present study is a narrative assessing the accomplishment of the Philippine Episcopal Diocese of Northern Philippines (EDNP) in her mission and ministry. It also investigates the problems which may be vital for the future of the diocese and provides opportunity for lay participation in the tasks, hence opening them to a new vision of the active role they are to play in the life and ministry of the church and the community. "-- The problem
A thesis submitted to the faculty of the seminary
In candidacy for the degree of Master in Divinity
Thesis (M.Div.)- St. Andrew's Theological Seminary, Quezon City